PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS XI IPA 4 MAN 1 PEKANBARU TAHUN PELAJARAN 2015/2016 - Filosofita Osi Rani; Susda Heleni; Jalinus ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to improve learning process and to increase the mathematic learning evaluation by implying Two Stay Two Stray type of cooperative model. Subjects of this research are XI IPA 4 students at MAN 1 Pekanbaru of 2015/2016. Total number of participant are 32 whose academic achievement are heterogen. This research have 2 cycles, each have four stages: planning, implementation, observation, and reflection. Each cycles closed by daily exam. The data collected by observation and examination at daily based. The data analised by narative descriptive analysis and statistical descriptive analysis. The implementation succes if the improvement of the learning process and the number of students reach KKM increase at daily examination I and daily examination II. The research result from the observation form shows that teacher and student activity are good after the treatment implemented. More than half students actively participated in the learning process, as discuss, presented LAS, responded to presenter group, and gave the learning conclusion. The students also tried to solve the quiz from teacher in a great manner. The number of students whose achieved basic score of KKM, daily examination I (first cycle), and daily examination II (second cycle) are 10 students (31.25%), 20 students (62.5%) and 24 students (75%). This research shows that implying Two Stay Two Stray type of cooperative model can improve learning process and increase mathematic learning evaluation for XI IPA 4 Students at MAN 1 Pekanbaru second semester of 2015/2016 to the basic competence (4.1) Using long polynomial division algorithm to determine the quotient and remainder of the division and (4.2) Using the remainder theorem and the factor theorem in solving the problem.Key Words: Mathematic learning evaluation, Two Stay Two Stray, Cooperative model